2020
DOI: 10.3390/ijms21239206
|View full text |Cite
|
Sign up to set email alerts
|

Length Polymorphism and Methylation Status of UPS29 Minisatellite of the ACAP3 Gene as Molecular Biomarker of Epilepsy. Sex Differences in Seizure Types and Symptoms

Abstract: Epilepsy is a neurological disease with different clinical forms and inter-individuals heterogeneity, which may be associated with genetic and/or epigenetic polymorphisms of tandem-repeated noncoding DNA. These polymorphisms may serve as predictive biomarkers of various forms of epilepsy. ACAP3 is the protein regulating morphogenesis of neurons and neuronal migration and is an integral component of important signaling pathways. This study aimed to carry out an association analysis of the length polymorphism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…According to previous studies 14,19,22 , we did not observe differences in methylation of Reelin, EPHX1 , or CPA6 in DRE. However, ACAP3 was hypomethylated in the cortex, as described previously 15 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…According to previous studies 14,19,22 , we did not observe differences in methylation of Reelin, EPHX1 , or CPA6 in DRE. However, ACAP3 was hypomethylated in the cortex, as described previously 15 .…”
Section: Discussionsupporting
confidence: 78%
“…In the present study we analyzed differential methylation associated with DRE. Unlike previous studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23] , we analyzed different tissues simultaneously, searched for markers of response to surgery, validated part of the results with an alternative technique and studied the epigenetic clock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [ 97 ] reported that TRPM2 was significantly regulated in diabetes and obesity. Findings were implied by Richter et al [ 98 ], Suchkova et al [ 99 ], Qureshi et al [ 100 ], Wang et al [ 101 ], Wang et al [ 102 ], Aoki-Suzuki et al [ 103 ], Ohno et al [ 104 ], Richter et al [ 98 ], Rahman and Copeland [ 105 ], Congiu et al [ 106 ], Ji et al [ 107 ], Wollmer et al [ 108 ], Yamazaki et al [ 109 ], Bardien et al [ 110 ], Comella Bolla et al [ 111 ], Horvath et al [ 112 ], Watanabe et al [ 113 ], Kushima et al [ 114 ], Grünblatt et al [ 115 ], and Sato and Kawata [ 116 ] when they found that TAOK2 , ACAP3 , PLXNA3 , PLXNA4 , DCTN1 , NTNG2 , LRP4 , AGRN (agrin), TAOK2 , POLG (DNA polymerase gamma, catalytic subunit), KCNK2 , OPRK1 , ABCA2 , ABCA7 , LRRK2 , CD200 , PAK3 , PADI2 , EPHB1 , CHAT (choline O-acetyltransferase) and SLC18A1 plays a substantial role in the patients with neurological and neuropsychiatric disorders. Studies showed that biomarkers include PLD2 [ 117 ], FLNA (filamin A) [ 118 ], SMURF1 [ 119 ], LINGO1 [ 120 ], CACNA1H [ 121 ], NLRP6 [ 122 ], NLRC3 [ 123 ], CXCR2 [ 124 ] and C5AR1 [ 125 ] plays an important role in progression of hypertension.…”
Section: Discussionmentioning
confidence: 73%
“…Sun et al [96] found that TRPM2 was significantly associated in obesity associated type 2 diabetes mellitus. Richter et al [97], Suchkova et al [98], Qureshi et al [99], Wang et al [100], Wang et al [101], Aoki-Suzuki et al [102], Ohno et al [103], Richter et al [104], Rahman and Copeland [105], Congiu et al [106], Ji et al [107], Wollmer et al [108], Yamazaki et al [109], Bardien et al [110], Comella Bolla et al [111], Horvath et al [112], Watanabe et al [113], Kushima et al [114], Grünblatt et al [115] and Sato and Kawata [116] have shown that TAOK2, ACAP3, PLXNA3, PLXNA4, DCTN1, NTNG2, LRP4, AGRN (agrin), TAOK2, POLG (DNA polymerase gamma, catalytic subunit), KCNK2, OPRK1, ABCA2, ABCA7, LRRK2, CD200, PAK3, PADI2, EPHB1, CHAT (choline O-acetyltransferase) and SLC18A1 key for progression of neurological and neuropsychiatric disorders, but these genes might be liable for obesity associated type 2 diabetes mellitus. PLD2 [117], FLNA (filamin A) [118], SMURF1 [119], LINGO1 [120], CACNA1H [121], NLRP6 [122], NLRC3 [123], CXCR2 [124] and C5AR1 [125] are involved in hypertension, but these genes might be essential for progression of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%